DISTRIBUTION OF SOME MICRONUTRIENTS AND THEIR CONCENTRATIONS ASSOCIATED WITH CALCIUM CARBONATE IN SOME SELECTED SOIL ORDERS IN NINAVA AND DUHOK PROVINCES - Adel Al-Taee; Ahmed S. AL-Taee (Mesopotamia Journal of Agriculture)
Concentrations of some trace elements (Iron, Manganese, Copper and Zink) associated with calcium carbonate have been studied in four locations from different  soil orders (Entisols و Aridisols و Mollisols و Vertisol). The purpose  of this work is study the pedogenic distribution of these elements. Results showed a clear increase in the concentrations of iron, copper and zinc in Zawita soil followed by Sumeel soil. However the soil in Al-Fadlia was exclusively showed a high content of manganese, due to the presence  of manganese oxides deposits in these soils. The soil of Hawi Al-Kanisa was marked by relatively low concentrations of trace elements associated with calcium carbonate.  The pedogenic distribution of these elements associated with calcium carbonate, the results showed homogeneous in iron concentrations with depth in  Zawita soil and increase with depth in Al-Fadlia soil, while concentration was slightly decreased with depth, then return to rise in Sumeel and Hawi Al-Kanisa soils.However soils of Zawita,Sumeel and Hawi Al-Kanisa showed a relative uniform distribution of manganese with depth, while highest concentrations was found in the third and fourth depths in Al-Fadlia soil. The elements copper and zinc associated with calcium carbonate did not show a specific behavior in pedogenic distribution in all  studied soils.